2007
DOI: 10.1093/jnci/djk033
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Different Microsatellite Marker Panels for Detection of Mismatch Repair–Deficient Colorectal Tumors

Abstract: The pentaplex panel of mononucleotide repeats performs better than the NCI panel for the detection of mismatch repair-deficient tumors. Simultaneous assessment of the instability of BAT26 and NR24 is as effective as use of the pentaplex panel for diagnosing mismatch repair deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 159 publications
(120 citation statements)
references
References 27 publications
6
110
1
1
Order By: Relevance
“…A large Spanish study recently found that simultaneous assessment of BAT-26 and another mononucleotide repeat marker, NR24, resulted in 96% sensitivity for the detection of loss of MMR protein expression. 35 Finally, in the present study we found a very high concordance (206 of 208, 99%) between MSI ϩ status determined by BAT-26 alone and complete loss of MMR expression (Table 3). Only 1 of 208 (0.5%) tumors showed complete loss of expression of an MMR protein (MSH6) in the absence of MSI ϩ (Table 3).…”
Section: 21supporting
confidence: 72%
“…A large Spanish study recently found that simultaneous assessment of BAT-26 and another mononucleotide repeat marker, NR24, resulted in 96% sensitivity for the detection of loss of MMR protein expression. 35 Finally, in the present study we found a very high concordance (206 of 208, 99%) between MSI ϩ status determined by BAT-26 alone and complete loss of MMR expression (Table 3). Only 1 of 208 (0.5%) tumors showed complete loss of expression of an MMR protein (MSH6) in the absence of MSI ϩ (Table 3).…”
Section: 21supporting
confidence: 72%
“…9 MSI was present when one of the two markers was unstable. IHC analysis of the four mismatch repair proteins MLH1, MSH2, MSH6, and PMS2 in tumor tissue was performed in all patients using tissue microarrays (TMAs) as described previously.…”
Section: Microsatellite Instability Immunohistochemical Staining Anmentioning
confidence: 99%
“…Having expanded our published series, we have now encountered 1 hMSH2-deficient case with stable BAT26 and unstable BAT25 out of a total of 155 BAT26-stable CRCs (148 of which are juvenile cases) retested for MSI with BAT25 (Figure 4). Very recently, a collaborative effort of the Gastrointestinal Oncology Group of the Spanish Gastroenterological Association readdressed the issue of the performance of different microsatellite panels for the detection of MMR-deficient CRCs (Xicola et al, 2007 A different problem is whether MSI can be missed because of inadequate tissue sampling. The recommendations for molecular genetic analyses of cancer apply to MS-status determination as well, with result reliability requiring that the tissue specimen contains a major proportion of neoplastic cells (at least >50%) (Aaltonen et al, 1998), eventually microdissecting cancer from stromal cells prior to DNA extraction .…”
Section: Improving the Standards For Msi Identification By Evaluatingmentioning
confidence: 99%
“…In any event, methods and interpretations most likely differ among research labs even in 2007, as two papers reported MSI-H prevalence of 9.9% (52 out of 527 CRCs (Xicola et al, 2007)) and 18.1% (98 out of 542 CRCs (Kim et al, 2007); P ¼ 0.0002 by w 2 -test), using the pentaplex and the Bethesda panel, respectively. The alternative explanation would be that the MSI phenotype has largely different prevalence in North American and European CRC patients.…”
Section: Improving the Standards For Msi Identification By Evaluatingmentioning
confidence: 99%